1997
DOI: 10.1017/s003382220001821x
|View full text |Cite
|
Sign up to set email alerts
|

Secular Variation of Δ14C During the Medieval Solar Maximum: A Progress Report

Abstract: ABSTRACT. The Earth is within the Contemporaneous Solar Maximum (CSM), analogous to the Medieval Solar Maximum (MSM). If this analogy is valid, solar activity will continue to increase well into the 21st century. We have completed 75 single-ring and 10 double-ring measurements from AD 1065 to AD 1150 to obtain information about solar activity during this postulated analog to solar activity during the MSM. e14C decreases steadily during the period AD 1065 to AD 1150 but with cyclical oscillations around the dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 14 publications
5
28
0
Order By: Relevance
“…The STD's 49.8 year cycle (near the 0.05 confidence level) may be associated with the 57.9 year periodicity of SSN (correspond to Fourth harmonic of Suess cycle). These periodic signals are also observed and reported by others [18,46,47,51,52]. The important low frequency signals (> 70 y) reported in other studies [33,51], such as the Gleissberg cycle of solar activity (often considered 88 year periodicity) that corresponds to our calculation of SSN's 96 year significant periodicity and Suess cycle (near 200 y) is not clearly detected in our STD.…”
Section: Effects Of Ssn On Tree Ringssupporting
confidence: 88%
See 1 more Smart Citation
“…The STD's 49.8 year cycle (near the 0.05 confidence level) may be associated with the 57.9 year periodicity of SSN (correspond to Fourth harmonic of Suess cycle). These periodic signals are also observed and reported by others [18,46,47,51,52]. The important low frequency signals (> 70 y) reported in other studies [33,51], such as the Gleissberg cycle of solar activity (often considered 88 year periodicity) that corresponds to our calculation of SSN's 96 year significant periodicity and Suess cycle (near 200 y) is not clearly detected in our STD.…”
Section: Effects Of Ssn On Tree Ringssupporting
confidence: 88%
“…These fluctuations are present in centurial and decadal time scales [36]. Other researchers have shown that there is good correlation between solar activity and tree rings [18,33,45,47,51,52], and an 11 year cycle was also found with a short lag time in growth ring series in trees [46]. The variation was commonly monitored through indices constructed from SST and air pressure at sea level [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…The periods between 8.1 and 12.4 years were related to solar cycle of 11 years, while the period of 23.0 year was related to the Hale cycle. They suggested that the period of 55.7 years might be related to the fourth harmonic of the Suess cycle as discussed by Damon et al (1997). On the other hand, they suggested that the period of 73.1 years was attributed to the Gleissberg cycle, and the period of 188.6 years was attributed to the Suess cycle of 200 years.…”
Section: Solar Influencesmentioning
confidence: 96%
“…Variability of the 14 C Correspondence to: V. A. Dergachev (v.dergachev@pop.ioffe.rssi.ru) concentration is proved by experimental research, see (e.g. Damon et al, 1998;Kromer et al, 1998).…”
Section: Introductionmentioning
confidence: 99%